Dampak Pengembangan Kawasan Agropolitan Berbasis Tanaman Pangan Pada Perekonomian Kabupaten Tulungagung: The Impact of Food Crop-Based Agropolitan Area Development on The Economy of Tulungagung Regency - Mubarokah, Mubarokah; Widayanti , Sri; Syah, Mirza Andrian (Jurnal Ilmiah Manajemen Agribisnis, 2024)
Agropolitan is one of the efforts to develop an economy based on the food crop subsector in Tulungagung Regency. The aims of this research are to describe the implementation of the agropolitan program in Tulungagung Regency and to analyze the impact of agropolitan development on the regional economy in Tulungagung Regency. This research applies a qualitative analysis method to analyze the impact of the implementation of the agropilitan program using shift share analysis. The results show that the implementation of the agropolitan program is running quite well, but its performance is quite slow. This is because the role of the agro-industry has not been well implemented. Efforts that need attention are fertilizer and alsintan assistance so that farmers receive the benefits of this program. PPLguidance is also very important to direct the optimal apply of fertilizers. The impact of agropolitan shows several indications of progress, which can be seen from the aggregate coefficient having a positive value of 3.08 and the differential component having a positive value of 1.29, meaning that the agricultural sector has competitiveness for the economy of Tulungagung Regency. The proportional differential calculation has a positive value, which indicates that the agricultural development program, namely agropolitan, is running well, as indicated by a value of 0.72. Lastly, the structural shift component, which has a positive value of 2.01, indicates that the agricultural sector is still a mainstay in labor absorption.